2006
DOI: 10.1002/ccd.20837
|View full text |Cite
|
Sign up to set email alerts
|

The performance of renal duplex ultrasonography for the detection of hemodynamically significant renal artery stenosis

Abstract: The measurement of PSV is not only noninvasive but also highly accurate in detecting patients who have hemodynamically significant RAS. The authors emphasize that an enthusiastic application of renal duplex ultrasonography, particularly the measurement of PSV, is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 48 publications
1
19
1
Order By: Relevance
“…A meta-analysis of 88 studies showed that peak systolic velocity was more accurate than renal-aortic ratio and acceleration index with a sensitivity of 85% and specificity of 92% [14]. In another study, peak systolic velocity was better correlated with translesional pressure gradient for hemodynamically significant renal artery stenosis compared to RAR and percent diameter stenosis [15]. Utilization of captopril, color coding can increase the reliability of the RDU [16,17].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A meta-analysis of 88 studies showed that peak systolic velocity was more accurate than renal-aortic ratio and acceleration index with a sensitivity of 85% and specificity of 92% [14]. In another study, peak systolic velocity was better correlated with translesional pressure gradient for hemodynamically significant renal artery stenosis compared to RAR and percent diameter stenosis [15]. Utilization of captopril, color coding can increase the reliability of the RDU [16,17].…”
Section: Discussionmentioning
confidence: 96%
“…Intimal FMD can present as focal webs or long tubular lesions which often make the angiographic assessment of the disease severity difficult. Utilization of RDU, intravascular ultrasound (IVUS) and/or hemodynamic assessment by pressure wire pullback gradient measurements during and after angioplasty is helpful to assess the clinically significant lesions and has become a standard practice in many centers [15,20,21]. In hemodynamically significant lesions assessment of peak systolic velocity with RDU can be an effective alternative to translesional pressure gradient measurement using 0.014 in.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thank Dr. Dieter for his comment on our article [1]. We analyzed the quadratic equation as well as linear equation between pressure gradient and peak systolic velocity.…”
Section: Rebuttalmentioning
confidence: 99%
“…The parameter most representative of >20 mmHg TLPG was PSV on renal duplex ultrasound, 35 in that PSV cut-off of 219 cm/s gave a correlation coefficient between TLPG and PSV as high as 0.74. Only a well-trained sonographer can produce reliable results on renal duplex tests.…”
Section: Predictors Of Sufficient Bp Response To Ptramentioning
confidence: 99%